2016
DOI: 10.1080/13561820.2016.1220929
|View full text |Cite
|
Sign up to set email alerts
|

Observation of interprofessional collaboration in primary care practice: A multiple case study

Abstract: Interprofessional collaboration (IPC) is known to improve and enhance care for people with complex healthcare and social care needs and is ideally anchored in primary care. Such care is complex, challenging, and often poorly undertaken. In countries such as Canada, the United Kingdom, the Netherlands, Australia, and New Zealand, primary care is provided predominantly via general practices, where groups of general practitioners and nurses typically work. Using a case study design, direct observations were made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 46 publications
8
60
0
5
Order By: Relevance
“…Primary health care is the pillar of the health care system, with interprofessional collaborative teams being increasingly considered a key tenet and an important means for providing quality primary health care services (Starfield et al , 2005; Samuelson et al , 2012; Pullon et al , 2016. While interprofessional collaboration is recognized as an essential aspect of care for patients with complex and chronic conditions (Reeves et al , 2011; Pullon et al, 2016), the evidence remains in its infancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary health care is the pillar of the health care system, with interprofessional collaborative teams being increasingly considered a key tenet and an important means for providing quality primary health care services (Starfield et al , 2005; Samuelson et al , 2012; Pullon et al , 2016. While interprofessional collaboration is recognized as an essential aspect of care for patients with complex and chronic conditions (Reeves et al , 2011; Pullon et al, 2016), the evidence remains in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…While interprofessional collaboration is recognized as an essential aspect of care for patients with complex and chronic conditions (Reeves et al , 2011; Pullon et al, 2016), the evidence remains in its infancy. For these reasons, policy makers in Canada and elsewhere have continued to call for greater integration of interprofessional team-based primary health care and the development of indicators that specifically recognize the value of this added lens (Hutchison et al , 2011; Ministry of Health and Long-Term Care, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…possible. Research has shown that an increase in collaboration between medical fields is linked with improved patient care, especially those with complex medical conditions (Pullon, Morgan, Macdonald, McKinlay, & Gray, 2016). In a study across primary care providers in New Zealand, aspects of interprofessional collaboration as simple as sharing a common space and having short interactions with co-workers provided increased positive relationships and care within the practice (Pullon et al, 2016).…”
Section: Quality Of Lifementioning
confidence: 99%
“…In a study across primary care providers in New Zealand, aspects of interprofessional collaboration as simple as sharing a common space and having short interactions with co-workers provided increased positive relationships and care within the practice (Pullon et al, 2016). This research showed that relationships between healthcare workers as a team and between the team or business and the community at large are contributing factors to improved care for patients with complicated social or health concerns (Pullon et al, 2016). Another study stresses the importance of communication and compassion for effective interprofessional collaboration (Rider et al, 2014).…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation